Tacrolimus repairs glomerular podocytes injury in rats with adriamycin induced nephropathy - CHEN Cai-ming; LI Yi-xia; LIN Jia-qun; WAN Jian-xin (Linchuang shenzangbing zazhi)
Objective To explore the repair effect of tacrolimus on podocyte injury in rats with adriamycin-induced nephropathy.Methods A rat model of a minimal lesion nephropathy was established by tail vein injection of adriamycin,and tacrolimus was used for intervention.Rats were randomly divided into control group,model group and tacrolimus treatment group.In each group,urine was collected on days 0,7,14,21,28,and 35,urine protein excretion was measured,and rats were sacrificed on day 35 to collect kidney specimens.Electron microscopy was used to observe the fusion of podocyte processes in each group.The glomeruli were stained with TUNEL assay.Wt-1 and caspase-3 were orientated and semi-quantitatively detected by immunohistochemistry or immunofluorescence to observe the podocyte numbers and the apoptosis of podocytes in rats.Results After injection of adriamycin through tail vein,the urine protein of rats increased significantly,the number of podocytes decreased significantly,and the foot podocyte processes were widely fused.Compared with the model group,rats in the tacrolimus treatment group had significantly reduced 24-hour urine protein,improved foot process fusion,and increased podocyte numbers.Compared with the control group,the expression of caspase-3 protein in the glomeruli of the model group was increased,and the TUNEL stain was deepened.Compared with the model group,the expression of caspase-3 in the glomeruli of the tacrolimus treatment group decreased,and the TUNEL positiveness rate decreased,indicating the apoptosis of podocytes decreased.Conclusions Tacrolimus can repair podocyte injury in rats with adriamycin-induced nephropathy,and its mechanism is related to the inhibition of podocyte apoptosis.